Violação gramatical e grau de legibilidade das demonstrações contábeis no Brasil - Rody, Paulo Henrique Amaral (2023)
The objective of this thesis is to analyze the association between the degree of readability and the level of grammatical violation of financial statements, considering the effects of grammatical violations on the textual quality of information from publicly traded companies listed on Brasil Bolsa Balcão - [B]³. The literature evidence lacks complementation regarding the textual and narrative part of explanatory notes and management reports, respectively, when compared with accounting numbers, considering that both documents are integral parts of the financial statements. In this thesis, the Grammatical Violation proxy is presented as a proxy capable of indirectly measuring the quality of accounting information, within an environment of information asymmetry and conflicts of interest between companies and investors. Grammatical Violation is defined as the presence of violations of grammatical norms, such as errors in punctuation, spelling, agreement and other writing errors in a text. In this thesis, the Grammatical Violation proxy was measured automatically via Python, both for document collection and for processing to generate variables. A low level of Grammatical Violation suggests a high level of quality of the financial statements and this can reduce the risks of misinterpretations by users, which can increase investor confidence in the capital allocation process. The Readability proxy is measured and applied to the same documents and also analyzed via Python. The sample comprises non-financial companies listed in [B]³, from the period 2010 to 2021 (twelve years). According to the numerical properties of the dependent variables, four econometric regression models were estimated using different estimators to increase the robustness of the results. The first model tested the relationship between Readability and Grammatical Violation, the second model tested the relationship between Grammatical Violation and Shareholder Return, the third model analyzed the relationship between Grammatical Violation and Republication of financial statements and the fourth model evaluated the relationship between Grammatical Violation and Results Management. The main results found stand out: the higher the level of Readability, on average, the lower the degree of Grammatical Violation of the companies; the larger the size of the company, on average, the lower the degree of Grammatical Violation of the financial statements; the greater the debt, on average, the greater the degree of Grammatical Violation of the companies' financial statements; companies audited by Big Four have a lower degree of Grammatical Violation of financial statements; the higher the level of Grammatical Violation, on average, the lower the companies' Share Return; companies with a higher level of Grammatical Violation are less likely to republish financial statements; and the higher the level of Grammatical Violation, on average, the higher the companies' level of Earnings Management. This thesis contributes to the literature as one of the few Brazilian studies in the area to use text processing and automation tools to interpret language patterns within the accounting environment. It also contributes by signaling that the level of Grammatical Violation of the financial statements can be used as an indicator of reliable accounting information and credibility, due to the reduction of informational asymmetry, capable of being obtained through this proxy.